The influence of long-range interaction on the structure of a two-dimensional multi scale potential system. (23rd May 2019) - Fomin, Yu D; Ryzhov, V N; Tsiok, E N
Abstract: We present the results of a computer simulation study of a finite temperature phase diagram of two-dimensional and quasi two-dimensional core-softened systems both taking into account long-range Coulomb-like forces and ignoring them. The system structure was determined from analysis of the behavior of radial distribution functions, order parameters and number of nearest neighbors. The system has been shown to have a large number of different phases. We have found that long-range forces substantially affected the structure and the melting point of the system at low and moderate densities, while at high densities the effect of long-range forces was negligible.